2019
DOI: 10.1186/s13293-019-0265-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of biological sex and sex hormones on bile acid synthesis and cholesterol homeostasis

Abstract: Obesity and elevated serum lipids are associated with a threefold increase in the risk of developing atherosclerosis, a condition that underlies stroke, myocardial infarction, and sudden cardiac death. Strategies that aim to reduce serum cholesterol through modulation of liver enzymes have been successful in decreasing the risk of developing atherosclerosis and reducing mortality. Statins, which inhibit cholesterol biosynthesis in the liver, are considered among the most successful compounds developed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 134 publications
(168 reference statements)
6
47
1
1
Order By: Relevance
“…Cholesterol is converted to bile acids, a major mechanism for removal of cholesterol from the body, through two primary molecular pathways with CYP7A1 being the rate limiting enzyme in the primary pathway (Dietschy and Turley 2002). In humans, the CYP7A1-mediated primary pathway accounts for 90% of bile acid production whereas it only accounts for 60% in mice (Phelps et al 2019). Further, CYP7A1 is a major factor regulating lipoprotein synthesis and assembly (Wang et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol is converted to bile acids, a major mechanism for removal of cholesterol from the body, through two primary molecular pathways with CYP7A1 being the rate limiting enzyme in the primary pathway (Dietschy and Turley 2002). In humans, the CYP7A1-mediated primary pathway accounts for 90% of bile acid production whereas it only accounts for 60% in mice (Phelps et al 2019). Further, CYP7A1 is a major factor regulating lipoprotein synthesis and assembly (Wang et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot fully exclude the possibility that the effects of CAP on GLP‐1 secretion may be mediated via pathways that do not involve BA/TGR5. In addition, there is a growing body of evidence for the sex differences in BA metabolism 44 . The size of BA pool of female mice is 60% larger and more hydrophobic than that in males and higher levels of fecal BAs are also observed in females 44‐46 and the composition of the bile acid pool is also sexually dimorphic with females producing more CDCA than males 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Though sex-specific differences in bile acid synthesis are reported 52 , such differences in bile acid homeostasis are not well characterized 53 . It is shown that cytochrome P450 enzymes are important for bile synthesis 52 and regulated in a sex-specific manner 54 , 55 . Bile acids activate the nuclear receptors farnesoid X receptor, pregnane X receptor and vitamin D receptor as well as the G-protein-coupled receptor TGR5.…”
Section: Discussionmentioning
confidence: 99%